Rancang Bangun Sistem Sewa Loker Berbasis Web Menggunakan Arduino Uno dan Sensor DHT11 - Afriadi Syah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Lockers are public facilities that play an important role in maintaining the security and order of belongings belonging to students and visitors in educational environments. This study designs a web-based locker rental system with a prototype consisting of three locker compartments controlled by an Arduino Uno microcontroller. The system uses a DHT11 sensor to detect the temperature inside the locker, a limit switch to monitor the door’s open/close status, a solenoid door lock as an electrically operated replacement for conventional keys, and a buzzer as a high-temperature indicator. The rental process begins by entering a mobile phone number, selecting a locker and rental duration, making a payment, and receiving a unique code via WhatsApp, which is then used to open or close the locker. Testing results show that the DHT11 sensor recorded temperatures ranging from 29.6°C to 65.8°C with an average accuracy rate of 97.56%, with respons time 0,33 seconds until door opened. DHT11 experienced a decrease in accuracy at temperatures above 60°C. Repeated access tests conducted 30 times achieved an 86.67% success rate, with four failures caused by slow response times. The buzzer functioned 100% effectively with a temperature threshold set at 40°C. These results demonstrate that the system operates automatically, accurately, and responsively according to the design, and has potential for further development.